Key terms in systemic functional linguistics - Matthiessen, Christian M. I. M. (Key terms series., 2010)
The field of Systemic Functional Linguistics is a social semiotic approach to language pioneered by M.A.K. Halliday, which has assumed a central importance in linguistics in recent years, anchored by a growing body of work. This book details the key terms, the key thinkers and the key texts in this field in an approachable, easy to understand and accessible manner. It is authored by leading names in the field and is aimed at undergraduates and postgraduates studying linguistics and language studies.